An eclectic approach to mixed instrumental ensemble in Singapore primary education - Yeo, Siew Cheng. (2009)
This research study was more explorative than hypothesis-testing in nature. The purpose of this research was to explore whether a specially-planned eclectic approach to music-making in the mixed instrumental ensemble would increase the level of music appreciation and musicianship of primary school students in Singapore schools. It was also an attempt to evoke more interest in active music-making in the mixed instrumental ensemble, deviating from the common practice of ensemble teachers "drilling" students for performances.